Clinical outcomes and quality of life 5 years after a randomized trial of concomitant or sequential phlebectomy following endovenous laser ablation for varicose veins. Issue 9 (11th June 2014) - El‐Sheikha, J.; Nandhra, S.; Carradice, D.; Wallace, T.; Samuel, N.; Smith, G. E.; Chetter, I. C.
<x xml:space="preserve">Abstract</x> Background Endovenous laser ablation (EVLA) is a popular treatment for superficial venous insufficiency. Debate continues regarding the optimal management of symptomatic varicose tributaries following ablation of the main saphenous trunk. This randomized trial compared the 5‐year outcomes of endovenous laser therapy with ambulatory phlebectomy (EVLTAP) with concomitant ambulatory phlebectomy, and EVLA alone with sequential treatment if required following a delay of at least 6 weeks. Methods Patients undergoing EVLA for great saphenous vein insufficiency were randomized to receive EVLTAP or EVLA alone with sequential phlebectomy, if required. Outcomes included disease‐specific quality of life (QoL) (Aberdeen Varicose Vein Questionnaire; AVVQ), requirement for secondary procedures, clinical severity (Venous Clinical Severity Score; VCSS), residual and recurrent varicose tributaries, and generic QoL. Patients were followed up for 5 years. Results Fifty patients were randomized equally into two parallel groups. The EVLTAP group had lower VCSS scores at 12 weeks (median 0 (i.q.r. 0–1) versus 2 (0–2); P <0·001), and lower AVVQ scores at 6 weeks (median 7·9 (i.q.r. 4·1–10·7) versus 13·5 (10·9–18·1); P < 0·001) and 12 weeks (2·0 (0·4–7·7) versus 9·6 (2·2–13·8); P = 0·015). VCSS and AVVQ scores were equivalent by 1 year, but only after 16 of 24 patients in the EVLA group, compared with one of 25 in the EVLTAP group (P < 0·001), had received a secondary intervention. From 1 to 5 years both groups had equivalent outcomes. Conclusion EVLA with either concomitant or sequential management of tributaries is acceptable treatment for symptomatic varicose veins, with both treatments achieving excellent results at 5 years. Concomitant treatment of varicosities is associated with optimal improvement in both clinical disease severity and QoL.